Malate dehydrogenase (sMDH) in Amazon cichlid fishes: evolutionary features - Farias, Izeni P.; Val, Vera Maria Fonseca Almeida e (Comparative Biochemistry and Physiology -- Part B: Biochemistry and, 1992)
1. 1. The sMDH isozyme system was studied in five species of cichlid fishes found in the Amazon hydrographic basin (Astronotus ocellatus, Cichla monoculus, Geophagus cff harreri, Cichlassoma severum and Mesonauta insignis). All studied specimens presented a six-banded electrophoretic pattern, suggesting the existence of three gene loci (sMDH-A*, sMDH-B1* and sMDH-B2*). 2. 2. Klebe's serial dilutions, thermostability tests and tissue specificity performed on the sMDH of studied species indicated no divergence between B1* and B2* loci products, suggesting that these genes probably undergo the same regulatory gene action and that the duplication event occurred recently, after A* and B* divergence. 3. 3. The appearance of the same characteristics in all specimens, and the chromosomic picture of the family, suggest the occurrence of an event of duplication "in tandem" in the ancestors of Amazon cichlids. © 1992.
Keywords: Isoenzyme; Malate Dehydrogenase; Animals Tissue; Evolution; Fish; Gene Duplication; Gene Locus; Nonhuman; Priority Journal; Protein Electrophoresis; Species Difference; Animalsia; Astronotus Ocellatus; Cichla; Cichlidae; Geophagus; Mesonauta Insignis; Pisces